SOIL MONITORING CYBER-PHYSICAL SYSTEM - HOVORUSHCHENKO, ТETIANA; VOICHUR, YURII; LYSENKO, SERGII; BACHUK, VYACHESLAV; PAIONK, ILLYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article justifies the choice of hardware and communication components for a cyber-physical soil monitoring system. For the lower level, a set of sensors was selected: Decagon 5TE for simultaneous measurement of humidity, temperature, and electrical conductivity; Bluelab Soil pH Pen for acidity; ECOFUEL Soil Nutrient Sensor for nutrients (N-P-K); and Eijkelkamp Soil Moisture Sensor for additional determination of soil density. For the middle level, the ESP32 microcontroller was selected due to its high computing power, energy efficiency, and low cost, which is optimal for autonomous operation. Wi-Fi was chosen as the communication standard, which provides high speed, flexibility, scalability, reliable data protection, and low latency, ideally meeting the needs of the system in real time.The architecture of a cyber-physical soil monitoring system has been developed, which is a comprehensive technology platform that combines physical sensors, software, network communications, and analytical algorithms to collect, process, and analyze real-time soil condition data, The system consists of three levels: lower (sensors that measure physicochemical parameters such as humidity, temperature, pH, nutrient composition, density, etc.), middle (controllers that collect and transmit data) and upper (analytical software for processing information, visualizing it and providing recommendations). The main goal of this system is to ensure accurate monitoring of soil characteristics in order to improve agricultural planning, efficient use of resources and increase the productivity of agricultural lands. Due to the ability to promptly detect changes in soil conditions, farmers can make informed decisions regarding irrigation, fertilization, crop rotation and other agrotechnical measures. In the context of climate change and growing requirements for food security, the implementation of such systems is critically important for the sustainable development of the agricultural sector.
Keywords: cyber-physical system; soil monitoring; sensors; controller; data transmission standard; hardware components; cyber-physical system architecture